2002
DOI: 10.1074/jbc.m108623200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Phosphatase 2A and Protein Kinase Cα Are Physically Associated and Are Involved in Pseudomonas aeruginosa-induced Interleukin 6 Production by Mast Cells

Abstract: Pulmonary infection with Pseudomonas aeruginosa is characterized by massive airway inflammation, which comprises significant cytokine production. Although mast cells are abundant in the lung and are potent sources of various cytokines, a role of mast cells in P. aeruginosa infection remains undefined, and P. aeruginosa-induced signaling mechanisms in mast cells have not been studied previously. Here we demonstrate that human cord blood-derived mast cells, mouse bone marrow-derived mast cells, and the mouse mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 64 publications
4
59
0
Order By: Relevance
“…However, current knowledge of MC cytokine production in the context of bacterial infection is extremely limited. In humans, TNF-␣ and IL-6 are the only previously reported cytokines produced by human MC after bacterial infection (17,31,32). We attempted to determine those P. aeruginosa-induced MC mediators responsible for enhanced human PMN transmigration across endothelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, current knowledge of MC cytokine production in the context of bacterial infection is extremely limited. In humans, TNF-␣ and IL-6 are the only previously reported cytokines produced by human MC after bacterial infection (17,31,32). We attempted to determine those P. aeruginosa-induced MC mediators responsible for enhanced human PMN transmigration across endothelium.…”
Section: Discussionmentioning
confidence: 99%
“…Highly purified CBMC were obtained by long-term culture of cord blood progenitor cells, as previously described (16,17). After Ͼ8 wk in culture, mature MC (Ͼ95% purity) were identified by their morphological features and the presence of metachromatic granules (toluidine blue staining).…”
Section: Mast Cellsmentioning
confidence: 99%
“…In the case of protein phosphorylation, macromolecular protein complexes may restrict access of kinases and phosphatases to specific microenvironments and position them to respond rapidly to appropriate signals. In recent years several kinases in addition to CaMKIV, including CK2, p70 S6 kinase, p21-activated kinase, Jak2, I ␤ kinase, and protein kinase C, have also been shown to interact with PP2A (27)(28)(29)(30)(31)(32)(33). However, in most of these cases details describing a precise functional link between the kinase and PP2A are lacking.…”
mentioning
confidence: 99%
“…Bacterial toxins may activate MCs which, in response to infection, release many mediators causing an increase in vascular permeability and in the expression of adhesion molecules or act chemotactically directly on neutrophils and eosinophils, and also produce anti-microbial peptides like cathelicidins and defensins. Activation of human mast cells has been demonstrated for Staphylococcus aureus and Pseudomonas aeruginosa, which are the most common isolates from chronic otitis media [37][38][39][40]. Chonmaitree et al [19] reported that histamine levels were higher in bacteria-positive than bacteria-negative effusions in acute otitis media.…”
Section: Discussionmentioning
confidence: 99%